(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
The article analyses unfinished sentences in the speech of men and women from perspective of gender and pragmatics. As an object of analyze the book “Bridget Jones’s Diaries” by Helen Fielding has been chosen because of its live dialogs. The investigation revealed that unfinished sentences are more typical for men rather than women, even though both genders use them for similar reason such as taking time to think and formulate their thoughts and express the intensity of speaker’s emotions.